ANALISIS SALURAN DISTRIBUSI (DISTRIBUTION CHANNEL) POLIKLINIK REHABILITASI MEDIK PADA FASE AWAL OPERASIONAL DI RUMAH SAKIT X - Wiwin Indriani; Tita Hariyanti; Ni Luh Putu (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Medical Rehabilitation Clinic was new program in X hospital. Creating new program automatically associated with marketing. Marketing procedure of new units requires information system to derive initial data as a capital for the preparation of a marketing plan. Marketing program identifies market segment of medical rehabilitation service as well as determines which segments provide greater opportunities. Marketers achieve market segment by distribution channels.. Distribution channel function to deliver products of medical rehabilitation services to patients. The purpose of this study to determine distribution channel of medical rehabilitation services. Data collecting from observation, primary data on medic rehabilitation unit in September 2017 and interviews to physicians and patients. Distribution channel function as deliver services products from medic rehabilitation to patients.